Association between serum lithium level and incidence of COVID-19 infection - De Picker, LJ; Leboyer, M; Geddes, JR; Morrens, M; Harrison, PJ; Taquet, M (Royal College of Psychiatrists, 2022)
An antiviral effect of lithium has been proposed, but never investigated for coronavirus disease 2019 (COVID-19). Using electronic health records of 26 554 patients with documented serum lithium levels during the pandemic, we show that the 6-month COVID-19 infection incidence was lower among matched patients with ‘therapeutic’ (0.50–1.00) versus ‘subtherapeutic’ (0.05–0.50) lithium levels (hazard ratio (HR) = 0.82, 95% CI 0.69–0.97, P = 0.017) and among patients with ‘therapeutic’ lithium levels versus matched patients using valproate (HR = 0.79, 95% CI 0.67–0.92, P = 0.0023). Lower rates of infection were observed for both new COVID-19 diagnoses and positive polymerase chain reaction tests, regardless of underlying psychiatric diagnosis and vaccination status.